Early or late radiotherapy following gross or subtotal resection for atypical meningiomas: Clinical outcomes and local control - Dohm, Ammoren (J Clin Neurosci, 2017)
We report a single institution series of surgery followed by either early adjuvant or late radiotherapy for atypical meningiomas (AM). AM patients, by WHO 2007 definition, underwent subtotal resection (STR) or gross total resection (GTR). Sixty-three of a total 115 patients then received fractionated or stereotactic radiation treatment, early adjuvant radiotherapy (≤4 months after surgery) or late radiotherapy (at the time of recurrence). Kaplan Meier method was used for survival analysis with competing risk analysis used to assess local failure. Overall survival (OS) at 1, 2, and 5 years for all patients was 87%, 85%, 66%, respectively. Progression free survival (PFS) at 1, 2, and 5 years for all patients was 65%, 30%, and 18%, respectively. OS at 1, 2, and 5 years was 75%, 72%, 55% for surgery alone, and 97%, 95%, 75% for surgery + radiotherapy (log-rank p-value = 0.0026). PFS at 1, 2, and 5 years for patients undergoing surgery without early adjuvant radiotherapy was 64%, 49%, and 27% versus 81%, 73%, and 59% for surgery + early adjuvant radiotherapy (log-rank p-value = 0.0026). The cumulative incidence of local failure at 1, 2, and 5 years for patients undergoing surgery without early External Beam Radiation Therapy (EBRT) was 18.7%, 35.0%, and 52.9%, respectively, versus 4.2%, 13.3%, and 20.0% for surgery and early EBRT (p-value = 0.02). Adjuvant radiotherapy improves OS in patients with AM. Early adjuvant radiotherapy improves PFS, likely due to the improvement in local control seen with early adjuvant EBRT.